Distribution of Surface Structures of the Ice Sheet in Mizuho Plateau - Yokoyama, K. (1978)
P(論文) Among the structural phenomena on the ice sheet, the structures with the dimensions of (10)^1-(10)^4m are called here "surface structures". The data of the surface structures obtained in Mizuro Plateau up to date were compiled and refined. The surface structures were classified into five major groups, according to their physical characteristics, A) flat surface, B) undulation (isolated), C) undulation (grouped), D) crevasse and crack, E) moraine and muddy band. These structures are made mostly by deformation of ice caused by movement of an ice sheet. Thus the distribution of the surface structures would be a reflection of stress condition of the ice sheet; stress condition is controlled by ice thickness, flow velocity and bedrock topography. Referring to steepness and frequency of surface structures, Mizuho Plateau was divided into four subdivisional regions, coastal region, transitional region, inland region and mountainous region. The surface structures in the coastal region and in the vicinity of exposed land are steeper and more frequent than those of inland. Such variation of the feature of the surface structures is well explained by the distribution of the above-mentioned three factors which control the stress condition of the ice sheet. This paper is an approach to a study on dynamics of the ice sheet. departmental bulletin paper